ANALISIS PERFORMA MENARA PENDINGIN MECHANICAL INDUCED DRAUGHT ALIRAN COUNTERFLOW PADA PEMBANGKIT LISTRIK TENAGA PANAS BUMI LAHENDONG UNIT 5 - Jeisi Meilita Walangitan; Cyrke Bujung; Farly Tumimomor (Jurnal FisTa : Fisika dan Terapannya, 2021)
In the geothermal power plant process, the main cooling water system is required to maximize the power plant, one of them is using the cooling tower. The Cooling Tower is an incredibly vital cooler. So, the performance must be noted is still in accordance with initial conditions. The purpose of this research is to determined the performance of Mechanical Induced Draught counterflow Cooling Tower in Lahendong Geothermal Power Plan Unit 5 with quantitative research for 7 days with 10 hours of operational work. In Lahendong Geothermal Power Plant Unit 5. The result of this research showed the performance of Mechanical Induced Draught Counterflow Cooling Tower in Lahendong Geothermal Power Plan Unit 5. The range increased up to 14.2 C, in the morning because of the high humidity, the effectiveness which also increases in the morning and the airflow conditions which still remain. So, this research will be concluded when the performance of Mechanical Induced Draught Counterflow Cooling Tower Geothermal Power Plant Unit 5 is still in normal operation conditions and needs to do Make-up Water amounts of 387.81 m3/h.